La práctica de valores en el proceso de formación del liderazgo transformacional de los estudiantes de la carrera de trabajo social de la facultad de ciencias sociales de la Universidad Técnica de Machala, en el período 2013-2014. - Pineda Armijos, Elsa Mariana (2015)
This research aims to determine the practice of values in the process of formation of transformational leadership to develop and strengthen active learning training for students studying social work, for instruments such as surveys, interviews were conducted with groups focus and observation of work, which were applied to 209 students studying social work faculty of social sciences at the Technical University of Machala.